THE ROLE OF PROBIOTIC AND SYNBIOTIC PREPARATIONS IN CONVALESCENT (RESTORATIVE) THERAPY FOR ACUTE INTESTINAL INFECTIONS (International journal of medical sciences, 2025)
Objective: To evaluate and compare the clinical and microbiological efficacy of a specific probiotic formulation versus a synbiotic preparation (probiotic + prebiotic) as adjunctive therapy during the convalescent phase of acute intestinal infections (AII) in children. Methods: A prospective, randomized, double-blind, placebo-controlled trial was conducted in 240 children (aged 1-5 years) hospitalized with AII (non-bacterial or confirmed Rotavirus). After initial stabilization (defined as cessation of vomiting and successful oral rehydration), patients were randomized into three groups (n=80 each): Group 1 (Placebo): Standard care + placebo; Group 2 (Probiotic): Standard care + Lactobacillus rhamnosus GG (LGG, 1x10^10 CFU/day); Group 3 (Synbiotic): Standard care + LGG (1x10^10 CFU/day) + Fructooligosaccharide (FOS, 5g/day). The intervention was administered for 10 days. The primary endpoint was the duration of post-randomization diarrhea. Secondary endpoints included duration of hospitalization, incidence of symptom recurrence within 14 days, and changes in gut microbiota composition (assessed by 16S rRNA gene sequencing of stool samples at baseline and day 10). Results: The median duration of post-randomization diarrhea was significantly shorter in the Synbiotic group (38.5 hours; IQR 24-50) compared to both the Probiotic group (51.0 hours; IQR 40-72; p=0.012) and the Placebo group (70.0 hours; IQR 52-94; p<0.001). The Probiotic group also showed a significant reduction compared to Placebo (p=0.005). Hospitalization was shorter in the Synbiotic group (p=0.03 vs. Placebo). Microbiome analysis at day 10 revealed that the Synbiotic group had a significantly greater increase in the relative abundance of Bifidobacterium spp. and Faecalibacterium prausnitzii (a key butyrate producer) compared to the Probiotic and Placebo groups (p<0.01). All interventions were well-tolerated. Conclusion: The use of adjunctive probiotic (LGG) therapy significantly shortens the duration of diarrhea in children recovering from AII. The addition of a prebiotic (FOS) to create a synbiotic formulation provides a superior clinical and microbiological benefit, accelerating clinical recovery and promoting a faster restoration of a healthy gut microbiome profile.